IMPLEMENTATION OF A DIGITAL TECHNOLOGY-BASED RESEARCH-BASED LEARNING MODEL IN PAIBP INSTRUCTION AT GLOBAL TALENT ISLAMIC SCHOOL PALEMBANG - Anisah Azzahra; Fitri Oviyanti; Asri Karolina (LP2M IAI Al-Khairat Pamekasan, 2026)
The development of digital technology has transformed teaching methods and learning media in schools. SMP Global Talent Islamic School Palembang implements a research-based learning (RBL) model that positions students as active researchers supported by digital tools in Islamic Religious Education and Character Education (PAIBP). This study examines how digital-based RBL is planned, implemented, and evaluated, and explores its role in fostering students’ active and critical learning skills. This research uses a qualitative case study approach. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Validity was ensured through prolonged engagement and credibility checks. Findings indicate that instructional planning is based on students’ needs, teachers’ competencies, curriculum alignment, learning instruments, and institutional support. The process integrates Islamic values, teacher professionalism, parental involvement, and responsible use of digital technology. RBL implementation includes three stages: exposure, experience, and capstone. Exposure fosters awareness and helps students define research topics. Experience is the core stage, where students conduct simple research under teacher guidance using digital tools. Capstone involves preparing and presenting digital scientific products. Evaluation covers process and outcome assessment through rubrics measuring engagement, content mastery, research quality, and learning effectiveness. Overall, digital-based RBL promotes active and critical learning aligned with 21st-century curriculum demands.